Ceiling of the Central Hall or the Mahamandapa (pillared hall) - Temples of India Project Team (Jio Institute, 2024)
The ceiling of the central hall or the mahamandapa (pillared hall) is of the nabhichchhanda variety, characterized by a band of five concentric overlapping circles decorated with lotus petals and other floral designs. The top of the ceiling is embellished with a full-blown lotus, complete with a padmakesara (stem-like) pendant.